Globalization and markets (GRP2): MTID program brochure - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
Would developing countries and their poor populations benefit from further trade liberalization under the World Trade Organization (WTO)? How have the different strands of globalization affected poverty and food security in developing countries? What policies should governments promote to improve the access of small farmers and traders to domestic, regional, and global markets?Agriculture plays a predominant role in the economies of developing countries. Any strategy for ending poverty and hunger in the developing world must center on rapid growth in the agricultural sector. However, increased agricultural productivity can also have an adverse effect on the poor by depressing commodity prices and farm incomes. Poorly functioning markets, weak domestic consumer demand, and lack of export opportunities constrain agricultural growth. Trade negotiations have long been accompanied by heated debates about the costs and benefits of global trade liberalization. Such debates have focused on whether freer trade promotes development and reduces poverty or penalizes the poor through stagnation and the worsening of global and national income distribution disparities.The Globalization and Markets Program's research helps policymakers and stakeholders in developing countries address the implications of trade liberalization and globalization. We strengthen the analytical capacities of developing countries and use research and outreach to improve those countries' positions at the global negotiating table. In industrialized nations, we inform governments and the public about the impacts the developed world can have on developing countries and the world's poor. The Program supports the adoption of policies to establish more efficient global food, nutrition, and agricultural systems.